Pengaruh Sikap Siswa pada Tata Tertib Terhadap Disiplin Sekolah dii SMK Pembangunan Bukittinggi - Ulfa Rohmatun Nafiah; Deswalantri Deswalantri (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
This research was conducted based on the problems that exist in the Bukittinggi Development Vocational School. Based on the results of interviews with two students of class XI, students still have a negative attitude such as not paying attention to the rules that exist at school which causes students to commit violations according to their own wishes. The violations that students usually commit are: dressing that is not in accordance with the provisions of the school on the grounds that students are happy and comfortable wearing clothes that are taken out of their pants. The purpose of this study is to see the great influence of the attitudes of class XI students on discipline towards school discipline at Development Vocational Schools Bukittinggi. The research method is regression with a quantitative approach. Regression to see the effect of two different variables. The population in the study were 82 class XI students. The research sample was 82 students of class XI who were taken using the total sampling technique. Data was collected using an instrument in the form of a questionnaire, and processed using data analysis techniques. The results of the research hypothesis test found that Fcount > Ftable (87.306 > 3.96) with a coefficient of determination of 52.2% with the remaining 47.8% being influenced by other factors, it can be concluded that H0 is rejected and Ha is accepted, which means there is a significant influence between attitudes class XI students on the discipline of student school discipline at the Bukittinggi Development Vocational School.